2021
DOI: 10.1002/adem.202100195
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Laser‐Induced Graphene Fabric from Silk and Its Application Examples for Flexible Sensor

Abstract: Laser‐induced graphene (LIG) with original macroscopic fabric structure, flexible characteristic, and minimum 40 Ω sq−1 sheet resistance is prepared by a two‐step method of heat treatment and laser direct writing (LDW) from a low‐cost and environmentally friendly silk fabric. The method can quickly control the electrical conductivity and mechanical properties of the product during processing. Laser parameters are adjusted by experiment to obtain an optimal about 40 Ω sq−1 sheet resistance. Finite element analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Additionally, the LIG has also been successfully realized on multiple natural and synthetic materials. As shown in Figure 1 , diverse substrates such as plants (i.e., woods, leaves, potato skins and coconut shells) [ 22 , 23 , 24 ], fabrics (i.e., Kevlar and silk) [ 24 , 25 , 26 , 27 ], papers (i.e., printing paper and PI paper) [ 28 , 29 , 30 ], and polymers (i.e., polyethylene terephthalate and phenolic resin) are transformed into graphene directly by laser irradiation [ 17 , 27 , 31 , 32 , 33 , 34 ]. The exceptional design ability in the electrical performances and the wide selection of carbon precursors demonstrate the potential of LIG in the fields such as flexible, large-scale, and biodegradable electronics.…”
Section: Fabrications Of Ligmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, the LIG has also been successfully realized on multiple natural and synthetic materials. As shown in Figure 1 , diverse substrates such as plants (i.e., woods, leaves, potato skins and coconut shells) [ 22 , 23 , 24 ], fabrics (i.e., Kevlar and silk) [ 24 , 25 , 26 , 27 ], papers (i.e., printing paper and PI paper) [ 28 , 29 , 30 ], and polymers (i.e., polyethylene terephthalate and phenolic resin) are transformed into graphene directly by laser irradiation [ 17 , 27 , 31 , 32 , 33 , 34 ]. The exceptional design ability in the electrical performances and the wide selection of carbon precursors demonstrate the potential of LIG in the fields such as flexible, large-scale, and biodegradable electronics.…”
Section: Fabrications Of Ligmentioning
confidence: 99%
“…Meanwhile, the conductivity, electrochemical performance [24,27,35,36], biocompatibility [37,38], and hydrophobicity [39][40][41] of LIG also have been systematically studied. A variety of LIG devices have been developed, including sensors [14][15][16][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], supercapacitors [17,[43][44][45][46][47][48][49][50][51][52][53][54][55], nanogenerators [54][55][56][57][58]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same multi-pass approach was later proposed by the same group to obtain LIG from an acrylate-based positive photoresist [47]. A twostep approach was also proposed by Li et al [48] starting from silk fabric, as they first heated the material to 350 • C and then exposed the same to a laser scribing process to obtain LIG, as witnessed by Raman spectroscopy. Because lignin is a common industrial byproduct, Mahmood et al demonstrated the direct conversion of such material to graphene using laser writing [49].…”
Section: Laser Synthesis Of Graphenementioning
confidence: 96%